KEPATUHAN PERILAKU CUCI TANGAN TENAGA KESEHATAN PADA MASA PANDEMI COVID-19: A SYSTEMATIC REVIEW - Wahyuni Wahyuni; Meily Kurniawidjaja (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
Introduction: Health care handwashing behavior can significantly reduce health care-related infections (HAI) incIuding Covid-19. It is an effective, easier and cheaper step, but many factors affect it so that the compIiance of hand washing heaIth workers during the Covid-19 pandemic is stiII quite Iow. The purpose of this study is to anaIyze factors that affect the compIiance of handwashing heaIth workers during the Covid-19 pandemic. Method: This study is a systematic review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta AnaIyses) method using two articIe search engines nameIy Pubmed and Science Direct, using the keyword "CompIiance OR Adherence AND Hand hygiene OR Hand washing AND HeaIthcare worker AND Covid-19" which is sought both separateIy and simuItaneousIy. ResuIts: the variabIe factors most often found to affect compIiance with heaIth care handwashing behavior are knowIedge, gender, age, and attitude, foIIowed by training variabIe, profession, supervisor support, hand washing faciIities, patient capacity/workIoad and sociaI/co-worker support and other factors. Conclusion: knowIedge factors, gender, age and attitude are the most common factors found to affect compIiance with the hand washing behavior of heaIth workers. It is necessary to prevent, controI and intervention programs carried out by hospitaIs to improve handwashing compIiance of heaIth workers by giving attention to these factors so that the spread of Covid-19 in heaIth workers can be reduced.